1990
DOI: 10.1143/jjap.29.l36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen-Potential-Controlled Annealing on the Superconducting Properties of (Bi, Pb)2Sr2Ca2Cu3Oy Thin Films

Abstract: The oxygen potential of thin films consisting of monophasic (Bi, Pb)2Sr2Ca2Cu3O y was controlled by annealing them under various oxygen partial pressures. The T c of (Bi, Pb)2Sr2Ca2Cu3O y was found to decrease monotonously with decreasing oxygen potential. However, T c did not change when annealed under higher oxygen pressure up to 2.9×104 torr. The carrier concentration was found to change with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is known that the Tc of the BSCCO superconductor either increases or decreases with decreasing the oxygen content (12-17, 36, 37). This phenomenon may be explained because the BSCCO superconductor with an optimum value of oxygen content can obtain the optimum carrier concentration which corresponds to the maximum Tc (37)(38)(39). In this study, it is suggested that for the film annealed above 500~ in an oxygen-free atmosphere the decomposition of the 2212 phase as well as the change of the carrier concentration have strong relevance to the degradation of the Tc of the film.…”
Section: Resultsmentioning
confidence: 79%
“…It is known that the Tc of the BSCCO superconductor either increases or decreases with decreasing the oxygen content (12-17, 36, 37). This phenomenon may be explained because the BSCCO superconductor with an optimum value of oxygen content can obtain the optimum carrier concentration which corresponds to the maximum Tc (37)(38)(39). In this study, it is suggested that for the film annealed above 500~ in an oxygen-free atmosphere the decomposition of the 2212 phase as well as the change of the carrier concentration have strong relevance to the degradation of the Tc of the film.…”
Section: Resultsmentioning
confidence: 79%
“…[1] that it is only the La(2:l:4) system that truly follows the entire curve in both ascending and descending parts of the plateau. Rare-earth-based (1:2:3) and Bi-based 2122 compounds do not follow the curve in the range where p^ > 0.25 which is clear from the corresponding references, from where the pertinent data are taken [3,5]. In fact there are no experimental points available to substantiate the descending part of the plateau.…”
mentioning
confidence: 90%
“…It is characterized by a plateau, with sharp bends at both sides. The relation is primarily based on the experimental results [2][3][4][5][6][7][8] and is depicted in Fig. 1 of Ref.…”
mentioning
confidence: 99%